Project Management Analysis of Manufacturing Laboratory Development by Considering Risk Factors - Adi Kusuma, Yudha; Citra Aria Bima, Alim (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
Laboratory construction project is a project owned by the University of XYZ Madiun. Laboratory construction has the goal of adding practice facilities to the industrial engineering department. Laboratory construction supports the offline learning process when students do practice activities. This project was carried out by PT ABC with a project value of Rp. 500.000.000. PT ABC was selected through an appointment stage by the project owner without a tender process. Laboratory construction process was built for 12 weeks. Laboratory construction process was built from early June 2021 until the end of August 2021. Manufacturing laboratory projects require a review of project management and risk management in their implementation so that project work can avoid delays in time. Project management analysis shows that the critical track is the activity of A-C-F-G with a total duration of 84 days and the probability of the project being completed is 96.16%. The calculation of the average profit obtained by project implementers is Rp 59.893.125. Risk management measurements show that high category risks are erratic weather, poor safety regulations in the field, and low levels of management discipline.